KONFLIK KEWENANGAN PENGELOLAAN KEPELABUHANAN DALAM PERSPEKTIF SISTEM ADMINISTRASI PEMERINTAHAN DAN OTONOMI DAERAH DI INDONESIA - Drs. Desi Fernanda (Jurnal Borneo Administrator, 2005)
Dispute between Central and Local Government on seaport management tends to be more frequent since the implementation of regional autonomy laws of 1999. The focal point of such conflict rests on how to evenly distribute the power and authority of seaport management among different level of government. From the perspective of public administration, this situation will lead not only to the fading of seaport services, it also leads to the creation of unconducive economic atmosphere in the whole country. Learning from Canada’s experience, this paper offers legal interpretation and possible actions to solve either existing or prospective conflicts.